Angustia frente a deleite en Primavera extremeña de Julio Llamazares: estrategias atenuantes del escritor gozoso durante los horrores de la pandemia (Altre Modernità, 2022)
This work by Julio Llamazares, halfway between chronicle and travel book, focuses on several main themes of the author, namely the description of nature, the longing for rural life and the importance of the natural environment. The Leonese writer takes advantage of the exceptional circumstance of the 2020 pandemic to chronicle his own experience during the spring of that year, which the author spent with his family in an isolated house in the middle of the fields in Extremadura. Faced with the collective trauma experienced by humanity, the author attends the glorious spectacle of the rebirth of nature, that he observes with both joy and embarrassment, since he enjoys himself in a moment of general anguish. In this paper we will study how the writer establishes a series of rhetorical strategies to protect his own image aimed at excusing himself before the reader, either through the use of concrete linguistic elements of attenuation in order to safeguard his face, or through the shield of the literary tradition, with the memory of a literary background (Boccaccio and Virgil, mainly) that brings together people in moments of anguish and retired life.
Keywords: Julio Llamazares; travel literature; linguistic attenuation